Modification of physical-chemical and ecological properties of starch as a result of its electron exposure - Litvyak, Vladinir V.; Batian, Anatoly N.; Kravchenko, Viacheslav A. (Journal of the Belarusian State University. Ecology, 2019)
It has been established that exposure of potato starch with accelerated electrons (a dose of 110 to 440 kGy) leads to a significant amorphization of its structure with preservation of morphology. At exposure doses of up to 440 kGy, there is a noticeable destruction of starch macromolecules, and the contribution of oxidizing processes is insignificant. Amorphization and destruction of chains of potato starch increase its acidity and solubility. The increase in total titrated acidity, which may be due to the formation of organic acids (oxalic, malic, lactic, acetic, citric and succinic). In the exposed starch, an accumulation of 5-hydroxymethylfurfural was observed with an exposed in the exposure dose. The physicochemical properties of exposed starch are not constant. After a certain time, the acidity and solubility of exposed starches are substantially reduced, until the starches are completely insoluble in water. The most optimal way to stabilize the physical and chemical properties may be contact drying on roller dryers or extrusion treatment of exposed starch together with dry ice (solid form of carbon dioxide), which is added in an amount of 1–3 % to the mass of solids. Preextrusion or contact drying of 30–40 % starch suspension on roller dryers at a temperature of 120–180 °C leads to gelatinization (destruction of starch granules) and may cause an increase in the effect of exposure due to an increase in possible recombination options for polymer chains of starch.
Keywords: accelerated electrons; modified starches; amorphization; destruction; solubility in cold water; inactivation of microflora